2009
DOI: 10.1016/j.nic.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sodium MR Imaging and Sodium Bioscales for the Management of Brain Tumors

Abstract: The standard of care for the comprehensive treatment of high-grade primary brain tumors includes surgery, radiation treatment and chemotherapy. Magnetic resonance (MR) imaging is involved in the initial diagnosis for detection and characterization of the lesion, focusing on size, location and its effect on surrounding brain and then on the heterogeneity of the signal characteristics, the presence of hemorrhage, MR perfusion characteristics and integrity of the blood-brain-barrier. These imaging properties have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 11 publications
3
57
0
Order By: Relevance
“…Thulborn et al [136] proposed to measure tissue sodium concentration (TSC) via 23 Na MRI (along with proton MRI) and cell volume fraction (CVF) for assessing diseased tissues in the brain (tumor, stroke). TSC is the volume fraction weighted mean of the intra-cellular sodium concentration ([Na] in = 10–15 mM) and the extra-cellular sodium concentration ([Na] ex = 140–150 mM).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Thulborn et al [136] proposed to measure tissue sodium concentration (TSC) via 23 Na MRI (along with proton MRI) and cell volume fraction (CVF) for assessing diseased tissues in the brain (tumor, stroke). TSC is the volume fraction weighted mean of the intra-cellular sodium concentration ([Na] in = 10–15 mM) and the extra-cellular sodium concentration ([Na] ex = 140–150 mM).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Alzheimer's disease Mellon et al, 2009), inflammatory and tumorous pathologies (e.g. Inglese et al, 2010;Mellon et al, 2009;Thulborn et al, 2009). Using sodium MR imaging we aimed to (i) study the sodium concentration levels in HD compared to a healthy control group, (ii) investigate the relationship between brain atrophy and sodium concentration levels, and (iii) determine potential associations between the sodium levels and clinical as well as genetic parameters in HD participants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Nagy et al and Cameron II et al have shown that reduced (Na+/K+) adenosine triphosphatase activity and altered Na+/H+ exchange kinetics, which lead to an increased intracellular sodium, are associated with malignancy [12,13]. Thulborn et al discussed the method as a potential therapy-monitoring tool [14,15] which could be easily transferred to other organs [16].…”
Section: Introductionmentioning
confidence: 99%